SISTEM PENJADWALAN KEHADIRAN SATPAM BERBASIS WEB DI PERUSAHAAN MOTOR JAKARTA - Rinaldy, Muhammad Yusuf; Widiartin, Tjatursari (Melek IT : Information Technology Journal, 2022)
The Web-Based Security Guard Attendance Scheduling System at the Jakarta Motor Production Company was builtto make it easier for the head of the security division to make attendance schedules to avoid collisions in attendanceschedules between security guards and the same attendance schedule. The system can randomize attendanceschedules, display active attendance schedules, and attendance schedule history. The results of the system testingworked well, making it easier for the head of the security division to make attendance schedules, see the history ofattendance schedules, make it easier for security guards to find out their attendance schedules so that they couldpatrol.